IZMJEŠTENI IDENTITETI U PROZI DAŠE DRNDIĆ (Philological Studies, 2019)
This paper analyzes four literary texts by Daša Drndić in order to research a construction of displaced identites. All these texts contain the autobiographically motivated narrative of displacement, illuminating its various phases and temporary points in cities like Toronto, Rijeka and Berlin. Parallely with this plot line I followed various other displaced voices clothed up in different discursive strategies, which are inevitable and obsessive follow-up to the autobiographical reflection, and identified them as a modernist narrative of exile and (forced) emigration. In contrast, the narrator develops a postmodern immigrant identity whose key features are homelessness, belonging nowhere, eradication, temporality and existence in in-between spaces (Bhabha).
Keywords: Daša Drndić, identity, displacement, exile, emigration/ immigration, in-between spaces